Phylogenetic relationships and mitochondrial DNA sequence evolution in the African rodent subfamily Otomyinae (Muridae) - Robinson, T.J. (University of Pretoria, 2013)
Thesis (DPhil (Zoology))--University of Pretoria, 2005.